SOME METHODS OF ECOLOGICAL CULTURE THROUGH GEOGRAPHICAL KNOWLEDGE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Ecological culture plays an important role in maintaining the balance between people and the environment. In the formation of this culture, geographical knowledge is one of the main tools for the development of environmental consciousness in students. Geography provides an opportunity to approach issues of natural resources, climate change and environmental protection. This article aims to determine the role of geographical knowledge in the development of ecological culture and consider effective methods. Nowadays, as a result of human activities, environmental damage factors are increasing, and global environmental problems are becoming acute. Environmental problems such as climate change, depletion of land and water resources, and air pollution have a negative impact not only on nature, but also on human health and quality of life. In solving these problems, great attention is paid to the need to develop ecological culture.